Non-coding RNA-Encoded Peptides/Proteins in Human Cancer: The Future for Cancer Therapy - Bakhti, Seyedeh Z.; Latifi-Navid, Saeid (Current Medicinal Chemistry, 2022)
Although non-coding RNAs (ncRNAs) were initially thought to be a class of RNA transcripts with no encoding capability, it has been established that some ncRNAs actually contain open reading frames (ORFs), which can be translated into micropeptides or microproteins. Recent studies have reported that ncRNAs-derived micropeptides/ microproteins have regulatory functions on various biological and oncological processes. Some of these micropeptides/microproteins act as tumor inhibitors and some as tumor inducers. Understanding the carcinogenic role of ncRNAs-encoded micropeptides/ microproteins seems to pose potential challenges to cancer research and offer promising practical perspectives on cancer treatment. In this review, we summarized the present information on the association of ncRNAs-derived micropeptides/microproteins with different types of human cancers. We also mentioned their carcinogenic mechanisms in cancer metabolism, signaling pathways, cell proliferation, angiogenesis, metastasis, and so on. Finally, we discussed the potential clinical value of these micropeptides/ microproteins and their potential use in the diagnosis and treatment of cancer. This information may help discover, optimize, and develop new tools based on biological micropeptides/ microproteins for the early diagnosis and development of anticancer drugs.
Keywords: LncRNAs